ASESMEN PENINGKATAN KUALITAS PENDIDIKAN DALAM KONTEKS MANAJEMEN BERBASIS SEKOLAH - Mira Marisa; Akmal Hawi; Maryamah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2021)
Education is part of a foundation in advancing a country. Education is made a big investment for developed countries. This of course relates to anyone who takes part in the scope of the unit. Currently, that education faces tremendous challenges, related to the quality of human resources. The human resources in question are the best teachers in improving the quality of education. In this regard, the type of research carried out is in the form of library research where the data sources are obtained through research journals, research reports, books and papers and the like that are library in nature. And the results of this study indicate that several things need to be pursued in improving the quality of education, namely, through an understanding for a teacher about the quality of himself that affects the quality of teacher professionalism. In addition, efforts to revise the teacher recruitment system must also apply the principles as they should.